CSR Dynamics in the Midst of Competing Injunctions: The case of Danone. Issue 1 (7th August 2018) - Marais, Magalie; Reynaud, Emmanuelle; Vilanova, Laurent
Abstract : This study examines how firms manage competing injunctions for corporate social responsibility (CSR) across time. We first develop a theory of CSR dynamics that accounts for the idea that a firm's actual CSR (what the firm does) and its professed CSR (what it says it does): (i) depend on both internal injunctions (a firm's identity orientation) and external injunctions (stakeholder demands); and (ii) are not necessarily constant over time, that is, there might be discernible phases of CSR. We illustrate our theory with a longitudinal case study of Danone, a French food‐processing company. We show that in the midst of conflicting injunctions, Danone adopted a multi‐phase strategy that consisted of proactively managing opponents in the short term to better impose CSR in the long term. During the different phases, decoupling actual from professed CSR was a key instrument to maintain organizational cohesion.